DIFFERENTIATED ACHONDRITES ASUKA 881371, AN ANGRITE, AND DIVNOE: NOBLE GASES, AGES, CHEMICAL COMPOSITION, AND RELATION TO OTHER METEORITES - Weigel A.; Eugster O.; Koeberl C.; Krahenbuhl U. (My University, 1997)
We present a study of the noble gas isotopic abundances in two achondrites, Divnoe and the Asuka 881371 angrite. For Divnoe, we also performed chemical analyses of the major elements and of some minor and trace elements that are relevant for the comparison with other meteorite types and for the interpretation of the noble gas data. Based on the cosmic-ray produced noble gases, an exposure age of 5.4 +/- 0.7 Ma for Asuka 881371 was obtained. This ejection time from the parent asteroid differs from those of the other three angrites--Angra dos Reis (55.5 Ma), LEW 86010 (17.6 Ma), and LEW 87051 (=<0.2 Ma). Whereas the U,Th-4He, and K-40Ar gas retention ages of Asuka 881371 are 3750 +/- 1000 Ma and 3910 +/- 500 Ma, respectively, we derive for the 244Pu-136Xe system, a formation age of 4533 +/- 40 Ma, which is contemporaneous with that of the other angrites Angra dos Reis and LEW 86010. For Divnoe the abundance patterns of the major lithophile, siderophile, refractory, and volatile elements, the isotopic abundance pattern for primordial trapped Xe, and the oxygen isotopes indicate that this unique meteorite is related to the brachinite achondrites. Assuming no pre-exposure to cosmic rays on the parent body, Divnoe's asteroid ejection event occurred 17.2 +/- 2.3 Ma ago.